PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP RETURN ON ASSET (ROA) PADA PT MATAHARI DEPARTEMENT STORE TBK PERIODE 2014-2023 - Assyifa Marsela Syawali Putri; Agus Supriatna (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the Current Ratio and Debt to Asset Ratio on Return On Assets. This research method uses quantitative research with descriptive analysis techniques and associative or relationship research. The data analysis methods used are descriptive analysis, descriptive statistical analysis, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, hypothesis test, coefficient of determination test. Partially, the Current Ratio has a significant effect on Return On Assets with a value of tcount > ttable (3.664 > 2.365) with a sig value of 0.008 < 0.05, while for partial Debt To Asset results there is a significant influence on Return On Assets with a value of tcount > ttable ( 2.375> 2.365) ) with a sig value of 0.049 < 0.05. The results of simultaneous testing of the Current Ratio and Debt To Asset Ratio show a significant influence on Return On Assets with a Fcount > Ftable value (9.561 > 4.74) with a sig value of 0.010 < 0.05. The coefficient of determination obtained an R Square value of 0.655, meaning that the Current Ratio and Debt to Asset Ratio together have an influential contribution of 65.5% to Return On Assets. Meanwhile, the remaining 34.5% is influenced by other variables outside this research